Personalcontrolling und kommunale Leiharbeit - Giese, Ronald; Zielbauer, Joachim (Personal Controlling and Municipal Employment, 2007)
The aim of the article is an assessment of national economy's bases that open up possibilities for economic growth and full employment. The authors describle flexible models of working and so-called job sharing. They propose the concentration of labour force in companies lending their workers to municipal jobs.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1161, s. 310-317